NMR Investigation of the Interaction between the RecQ C-Terminal Domain of Human Bloom Syndrome Protein and G-Quadruplex DNA from the Human c-Myc Promoter. Issue 4 (15th February 2019) - Lee, Sungjin; Lee, Ae-Ree; Ryu, Kyoung-Seok; Lee, Joon-Hwa; Park, Chin-Ju
Abstract: Bloom syndrome protein (BLM) is one of five human RecQ helicases that participate in DNA metabolism. RecQ C-terminal (RQC) domain is the main DNA binding module of BLM and specifically recognizes G-quadruplex (G4) DNA structures. Because G4 processing by BLM is essential for regulating replication and transcription, both G4 and BLM are considered as potential targets for anticancer therapy. Although several studies have revealed the detailed mechanism of G4 unwinding by BLM, the initial recognition of the G4 structure by the RQC domain is unclear. Here, we investigated the interaction between BLM RQC and the G4 DNA from the c-Myc promoter by NMR spectroscopy. While the signals broadened upon reciprocal titrations, the β-wing of RQC had significant chemical shift perturbations and experienced millisecond timescale dynamics upon G4 binding. A point mutation in the β-wing (N1164A) reduced G4 binding affinity. Our hydrogen–deuterium exchange data indicate that imino protons of G4 were exchanged with deuterium much faster in the presence of RQC. We suggest that RQC binds to G4 by using the β-wing as a separating pin to destabilize the G4. By providing information about the RQC–G4 interaction, our study yields insight into potential strategies for preventing G4 processing by BLM. Graphical Abstract: Unlabelled Image Highlights: RecQ C-terminal (RQC) domain of Bloom syndrome protein (BLM) binds to the G-quadruplex with micromolar K d . β-wing and α2 region of the RQC domain play an important role in the G-quadruplex interaction. BLM RQC domain destabilizes G-quadruplex without the helicase domain of the protein. Our results contribute to the understanding of the initial G4 recognition process of BLM.